2021
DOI: 10.1016/j.neurobiolaging.2021.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic proteins associated with cognitive performance and neuropathology in older humans revealed by multiplexed fractionated proteomics

Abstract: Alzheimer’s disease (AD) is defined by the presence of abundant amyloid- β (A β ) and tau neuropathology. While this neuropathology is necessary for AD diagnosis, it is not sufficient for causing cognitive impairment. Up to one third of community dwelling older adults harbor intermediate to high levels of AD neuropathology at death yet demonstrate no significant cognitive impairment. Conversely, there are individuals who exhibit dementia with no gross explanatory n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 87 publications
(122 reference statements)
1
45
1
Order By: Relevance
“…To confirm that our dataset profiled an enriched synaptic proteome, we performed several alignment and enrichment analyses. Firstly, we aligned our filtered dataset with two recent human brain and synapse proteome studies [33,34]. This revealed >99% of our dataset matched recently published data (Figure 1B).…”
Section: Resultsmentioning
confidence: 56%
“…To confirm that our dataset profiled an enriched synaptic proteome, we performed several alignment and enrichment analyses. Firstly, we aligned our filtered dataset with two recent human brain and synapse proteome studies [33,34]. This revealed >99% of our dataset matched recently published data (Figure 1B).…”
Section: Resultsmentioning
confidence: 56%
“… 13 and added pre- and post-synaptic terms from an inclusion list generated in Carlyle et al . 4 ( Supplementary Table 4 ). We generated an organelle marker map by performing a PCA on all proteins across all samples.…”
Section: Resultsmentioning
confidence: 99%
“… 8 recently showed that enrichment of mitochondrial, myelin sheath and synaptosomal fractions from transgenic Alzheimer’s disease mouse model tissue was able to identify compartment-specific alterations in disease-relevant pathways such as metabolism and synaptic dysfunction. Carlyle et al 4 furthermore showed that enrichment of synaptosomes from post-mortem human brain tissue revealed a number of targets selectively associated with cognitive impairment in older individuals that were not revealed by whole-tissue studies. These studies indicate the potential value of broader subcellular profiling of the Alzheimer’s disease brain.…”
Section: Introductionmentioning
confidence: 99%
“…Change in brain protein expression in AD versus controls was determined using our in-house developed database—NeuroPro—which combines results from 33 previous studies that used proteomics to identify consistent protein differences between AD and control human brain tissue [ 11 , 12 , 41 , 44 73 ].…”
Section: Methodsmentioning
confidence: 99%